A Câmara escura: Gestão Territorial e novas territorialidades do Capital em Goiás - MORAES, Robson de Sousa (2011)
The present dissertation aims at deciphering the territorial insertion of Goiás into the Capital globalization phenomenon. The gradual capture of the goiana land by the Capital in movement is uncurtained by the concepts of the territory as well as territorial management, which are seen as fundamental elements for the construction of a solid geographical interpretation of the contemporary period of Goiania. The actions of the state and federal executive power, focusing on the incoporation of a productive system, existing in Goiás, provoked expressive impacts in territorial configuration of the state, triggering meaningfull tranformations into the control and into the territory management. The planetary expansion of the capitalist perspective injected a new social and economic dynamics which changed the existing characteristics of the goiana land. The current hegemony of the globalized Capital imposes, in Goiás, a form of appropriation and territorial management, which reinforces its capture, configurating it according to its demands, exercising actions that indicate a conception and the use of the space with a strong economic character, however, with varied social implications.